PENGARUH PENGGUNAAN METODE SQ3R (SURVEY, QUESTION, READ, RECITE, REVIEW) TERHADAP KREATIVITAS DAN HASIL BELAJAR SISWA MATA PELAJARAN IPS EKONOMI DI SMPN 2 KOTA JAMBI: Creativity, Learning Outcomes, SQ3R method - Sondarti, Vepy (JURNAL AKADEMIKA, 2018)
SQ3R method is an approach used by teachers to create conditions for active learning and help students master the material more lessons learned, using the learning steps ranging from viewing the subject in outline, make some inquiries, actively reading to find the answers, say again, and repeat the whole. While the expository method in which teachers prepare teaching materials in advance and communicated to students, the teacher is the sole source of study, students who received the information. Creativity is the ability to produce a composition, product, or idea of ​​what is basically a new and previously unknown author.